FAMSS BAG / Muhammad Firdaus Ibrahim … [et al.] - Ibrahim, Muhammad Firdaus; Mohd Zari, Suha Fatinah; Aziz, Alia Sofiah; Suhaimi, Nur Fatihahtul Shamimi; Bujairimi, Muhammad Aiman Safwan (2021)
The name of our company is FAMSS BAG. The idea to apply the advancement of technology that of the bag in Malaysia was come from five people. We thought that the idea of combining the technology and bag will be a great business in Malaysia. This is because they are no business yet that combine technology and bag in Malaysia. It will bring a great profit for this type of business. Malaysia as well as other developing countries has the business sector which has an enormous potential for improving the nation economy and income. Because of this positive development, we find ourselves interested in getting involved in the business sector. As we have seen, there are a lot of businesses in Malaysia, especially in the fashion and technology, so we take this opportunity to bring out our name, which is FAMSS BAG.